Pengaruh Model Pembelajaran Polya Terhadap Hasil Belajar Matematika Kelas IV UPTD SDN Sepulu 1 Kabupaten Bangkalan - Elvira Maulina; Conny Dian Sumadi (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
The purpose of this study was to determine the significant effect of applying the Polya model to the learning outcomes of fourth grade students at UPTD SDN Sepulu 1, Bangkalan Regency. This research is a quasi-experimental research with a nonequevalent control group design. The population of this study were students of class IV UPTD SDN Sepulu 1. Sampling used a saturated sampling technique, because the total population was <100. The research samples used were class IV-A with 22 students as the control class and class IV-B with 22 students as the experimental class. The data analysis technique for testing the hypothesis of students' mathematics learning outcomes uses the Mann Whitney test with the SPSS program. The Mann Whitney test belongs to the group of nonparametric statistics. The Mann Whitney test was used to test two independent groups. The results of testing the hypothesis obtained an Asymp sig.(2-tailed) value of 0.000 where 0.000 <0.05 then H0 is rejected and Ha is accepted. Based on the results of the hypothesis testing, it can be concluded that there is a significant difference between the experimental group and the control group, so the treatment given has a significant effect on the Polya model on the mathematics learning outcomes of fourth grade students of UPTD SDN Sepulu 1, Bangkalan Regency.